(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of rhizosphre of different tree species on germination and growth of rough lemon and Rangpur lime rootstocks at Dr Panjabrao Krishi Vidyalaya, Nagpur, during 2014- 15. The rhizosphere properties of different trees showed maximum organic carbon in rhizosphere soil of banyan tree (Ficus benghalensis L.) soil (0.90%), while CaCO3 was maximum in mango (Mangifera indica L.) tree rhizosphere soil. The KMnO4-N (254.0 kg/ha), NH4OAc (369.6 kg/ha) and CaCl2-S (9.6 kg/ha) were found maximum in Nagpur mandarin tree rhizosphere soil. The available phosphorus Olsen-P was found maximum in banyan tree rhizosphere soil (15.3 kg/ha), in addition to NH4OAc -Ca and NH4OAc -Mg. The maximum bacterial colonies (42.4×10³ cfu/g) were observed in Nagpur mandarin (Citrus reticulate Blanco) tree rhizosphere soil. Fungal colonies on other hand, were found maximum in banyan tree rhizosphere soil (26.6×10³ cfu/g). The germination of rough lemon and Rangpur lime seeds was maximum in Nagpur mandarin rhizosphere soil than in bulk field soil. The growth parameters like plant height (3.90 cm) and number of leaves/seedling (2.00) were maximum in Nagpur mandarin tree rhizosphere soil due to presence of native homologous microorganisms in Nagpur mandarin tree rhizosphere soil.